Neutralizing antibody titers over 12 months after SARS-CoV-2 mRNA vaccine booster in patients with relapsing multiple sclerosis continuously treated with ofatumumab - Tjalf Ziemssen; Marie Groth; Benjamin Ettle; Tobias Bopp (Human Vaccines & Immunotherapeutics)
Booster vaccinations against SARS-CoV-2 are recommended 6–12 months after the last dose or infection in elderly and high-risk groups. The present analysis aims to evaluate whether an interval shorter than 12 months is required in multiple sclerosis patients receiving ofatumumab. Neutralizing antibody status over 1 year in patients receiving booster vaccination in the non-interventional, multicenter KYRIOS study under continued ofatumumab treatment was analyzed. Fifteen patients were included. At the time of the first booster vaccination, ten patients were seropositive for neutralizing antibodies, four patients were seronegative, and for one patient, no baseline levels were available. All patients who were seropositive at baseline showed >2-fold increase in neutralizing antibody titers after the first booster and two patients (20%) showed a >10-fold increase. Among seronegative patients, three (75%) had a >10-fold increase in neutralizing antibody titers. Seropositivity was maintained in almost all patients until month 12. One initially seronegative patient had less than 2-fold increase in neutralizing antibody titers after the booster vaccination and can be considered a non-responder. Most patients with continued ofatumumab treatment are able to maintain permanent seropositivity and therefore presumably constant protection against severe courses of COVID-19 if repeated booster vaccinations are applied.